INGO - subjects of international law: public or private? - Kh M Dzhantaev (RUDN Journal of Law, 2012)
Leaning against works of leaders domestic civilists and corresponding international legal documents of last years, the author opens character and the nature of the relations regulated by so-called conflict norms of the international private law. Then compares them to the legal relationship making a subject of activity of the international non-governmental organizations. Such approach allows it to result weighty arguments in favor of their international legal personality.